2017
DOI: 10.1093/hmg/ddx292
|View full text |Cite
|
Sign up to set email alerts
|

Primary angle closure glaucoma (PACG) susceptibility gene PLEKHA7 encodes a novel Rac1/Cdc42 GAP that modulates cell migration and blood-aqueous barrier function

Abstract: PLEKHA7, a gene recently associated with primary angle closure glaucoma (PACG), encodes an apical junctional protein expressed in components of the blood aqueous barrier (BAB). We found that PLEKHA7 is down-regulated in lens epithelial cells and in iris tissue of PACG patients. PLEKHA7 expression also correlated with the C risk allele of the sentinel SNP rs11024102 with the risk allele carrier groups having significantly reduced PLEKHA7 levels compared to non-risk allele carriers. Silencing of PLEKHA7 in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 68 publications
2
16
0
1
Order By: Relevance
“…The precise molecular mechanisms through which PLEKHA7 is implicated in disease (5, 6), morphogenesis (8, 23), and diverse cellular functions ( 9 11 ) are poorly understood. Here we address the structure-function relationships of the N-terminal tandem WW domains of PLEKHA7, a critically important region for the ability of PLEKHA7 to scaffold and cluster transmembrane proteins ( 13 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise molecular mechanisms through which PLEKHA7 is implicated in disease (5, 6), morphogenesis (8, 23), and diverse cellular functions ( 9 11 ) are poorly understood. Here we address the structure-function relationships of the N-terminal tandem WW domains of PLEKHA7, a critically important region for the ability of PLEKHA7 to scaffold and cluster transmembrane proteins ( 13 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a zebrafish model, the PLEKHA7 homolog Hadp1 is required for cardiac morphogenesis and contractility ( 8 ). PLEKHA7 has also been involved in the control of microRNA processing ( 9 , 10 ) and Rho GTPase activity ( 11 ). In cultured cells and mice, PLEKHA7 is required to make cells more susceptible to the cytotoxic effects of Staphylococcus aureus α-toxin, through a mechanism that involves junctional clustering of ADAM10, mediated by tetraspanin 33 (Tspan33) ( 12 , 13 ).…”
mentioning
confidence: 99%
“…Pathogenic mutations in this gene can result in type II Stickler syndrome and Marshall syndrome [6, 7], while rs1676486 on COL11A1 is associated with lumbar disc herniation susceptibility [8]. Pleckstrin homology domain-containing family A member 7 (PLEKHA7) is an adherens junction protein [9] required for organizing the epithelial architecture and contributes to tissue homeostasis. Since it is likely involved in regulating fluid flow across the inner wall of the Schlemm's canal [10], it was proposed that mutations in this gene could affect fluid dynamics in the pathophysiology of angle-closure glaucoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…PLEKHA7 encodes an apical junctional protein that is expressed in the non-pigmented ciliary epithelium, a key component of the blood aqueous barrier (BAB). Lee et al found that PLEKHA7 is down regulated in the iris of PACG patients that carry the C risk allele at SNP 11024102 [13]. Silencing of PLEKHA7 in non-pigmented ciliary epithelium (NPCE) affected actin cytoskeleton organization in vitro.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Variants in PLEKHA7, an adherens junction protein, increase the risk of sudden, symptomatic pressure rises in PACG [10]. This protein is expressed in iris, ciliary body, and choroid [12] and has GTPaseactivating protein (GAP) activity [13]. SNPs in other candidate genes, including HGF (hepatocyte growth factor) [14], HSP70 (heat-shock protein 70) [15], MFRP (membrane type frizzled related protein) [16], eNOS (endothelial nitric oxide synthase) [15] and MMP9 (matrix metalloproteinase-9) [17] also have significant association with PACG.…”
Section: Introductionmentioning
confidence: 99%